2016
DOI: 10.1515/jci-2015-0018
|View full text |Cite
|
Sign up to set email alerts
|

A Conditional Randomization Test to Account for Covariate Imbalance in Randomized Experiments

Abstract: We consider the conditional randomization test as a way to account for covariate imbalance in randomized experiments. The test accounts for covariate imbalance by comparing the observed test statistic to the null distribution of the test statistic conditional on the observed covariate imbalance. We prove that the conditional randomization test has the correct significance level and introduce original notation to describe covariate balance more formally. Through simulation, we verify that conditional randomizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 35 publications
1
48
0
Order By: Relevance
“…This gives a conditional randomization test. Zheng and Zelen (2008) and Hennessy et al (2016) demonstrated that conditional randomization tests often improve the power as long as the covariates are predictive of the outcomes. Holt and Smith (1979) and Miratrix et al (2013) discussed post-stratification, the estimation analog of testing.…”
Section: The Above Null Hypothesis Must Satisfymentioning
confidence: 99%
“…This gives a conditional randomization test. Zheng and Zelen (2008) and Hennessy et al (2016) demonstrated that conditional randomization tests often improve the power as long as the covariates are predictive of the outcomes. Holt and Smith (1979) and Miratrix et al (2013) discussed post-stratification, the estimation analog of testing.…”
Section: The Above Null Hypothesis Must Satisfymentioning
confidence: 99%
“…(2) the true propensity score model is a logistic regression model, and (3) the collection of covariates is sufficient for the logistic regression model. More recently, Hennessy et al (2016) proposed a conditional randomization test for randomized experiments that is similar to Rosenbaum (1984) in that it also permutes within groups of units with the same covariate values, but it does not require any kind of model specification. Rosenbaum (1984) and Hennessy et al (2016) only consider cases with categorical covariates, and they make connections between their randomization tests and adjustment methods for categorical covariates, such as post-stratification (Miratrix et al, 2013).…”
Section: Accounting For Covariate Balance In Randomization Testsmentioning
confidence: 99%
“…() for network dependence and Hennessy et al . () for covariate imbalance. In such cases it is sometimes possible to develop non‐uniform randomization schemes that result in valid p ‐values, as with the CPT and the CRT.…”
Section: Introductionmentioning
confidence: 99%